Vanadium salt inhibits osteoclast formation and preserves bone integrity in a rat model of type-1 diabetes associated bone loss - Joshua Greendyk; James Thornton; Darian Napoleon; Michael Greenberg; Anthony Lin; Mike Levidy; Jonathan R. Lopez; Maximilian Muñoz; Kevin Innella; Yazan Kadkoy; Maya Deza Culbertson; Jessica A. Cottrell; et al. (BioMetals, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Energy and environmental benefits of truck platooning for a busy freight corridor - Brian R. McAuliffe; Sean McTavish; Arash Raeesi; Sheldon Harrison (Transportation Research Part D: Transport and Environment, 2025)

Fossil leaf cuticle: Best practices for preparation and paleo-CO2 analysis - Xiaoqing Zhang; Dana L. Royer; Carina E. Colombi; Juan Martin Drovandi; Jennifer C. McElwain; Gaëtan Guignard; Qin Leng; Barry H. Lomax; Nathan D. Sheldon; Rebekah A. Stein; Garland R. Upchurch; Yongdong Wang; et al. (Earth-Science Reviews, 2025)

Continental Connections: Changing Temperature, Wind and Precipitation Advance the Postbreeding Roosting Phenology of Avian Aerial Insectivores - Yuting Deng; Birgen Haest; Maria C. T. D. Belotti; Wenlong Zhao; Gustavo Perez; Elske K. Tielens; Daniel R. Sheldon; Subhransu Maji; Jeffrey F. Kelly; Kyle G. Horton (Global Ecology and Biogeography, 2025)
Aim Migratory birds are under threat by climate change. Successfully conserving them requires knowing which climatic factors drive changes in their migratory behaviour. Weather conditions may directly or indirectly affect the temporally disjointed life history stages of migratory birds, including the breeding, roosting and nonbreeding stages. However, the influences of these broad‐scale patterns are often not studied together. Coupling migratory bird movements estimated using weather radar (NEXRAD) with long‐term and large‐scale environmental data allows us to overcome these spatiotemporal uncertainties. Here, we assess environmental drivers of the phenology of postbreeding roosting of aerial insectivores in the Great Lakes region (USA) by evaluating predictors during the months leading up to roosting across species' ranges. Location Northern United States and Canada. Time Period 21‐year (2000–2020). Major Taxa Studied Avian aerial insectivores. Methods We conducted a spatially explicit time‐window analysis to examine the effects of 17 gridded weather and vegetation variables on swallow peak roosting phenology in the Great Lakes, making minimal ecological assumptions. Results We found that peak roosting timing is paced by both local conditions (headwind at 850 hPa) at the Great Lakes and distant conditions (minimum temperature, precipitation rate and specific humidity) at the likely breeding and stopover sites, with warmer temperatures advancing, headwind delaying and high precipitation advancing the phenophases. Time windows selected for the possible breeding and stopover sites are mostly before or around the time of roosting, with one exception during wintertime. Main Conclusions Although climatic shifts play a significant role in driving variation in phenology, for migratory species, the proximate driver can originate hundreds to thousands of kilometres away, and potentially months prior. Our study illuminates these far‐reaching patterns in aerial insectivores, enhancing our grasp of migration ecology and paving the way for a more comprehensive understanding of hemispheric animal movements.

Positive Feedback on Climate Warming by Stream Microbial Decomposers Indicated by a Global Space‐For‐Time Substitution Study - Javier Pérez; Luz Boyero; Richard G. Pearson; Mark O. Gessner; Alan Tonin; Naiara López‐Rojo; Juan Rubio‐Ríos; Francisco Correa‐Araneda; Alberto Alonso; Aydeé Cornejo; Ricardo J. Albariño; Sankarappan Anbalagan; et al. (Global Change Biology, 2025)
Decomposition of plant litter is a key ecological process in streams, whose contribution to the global carbon cycle is large relative to their extent on Earth. We examined the mechanisms underlying the temperature sensitivity (TS) of instream decomposition and forecast effects of climate warming on this process. Comparing data from 41 globally distributed sites, we assessed the TS of microbial and total decomposition using litter of nine plant species combined in six mixtures. Microbial decomposition conformed to the metabolic theory of ecology and its TS was consistently higher than that of total decomposition, which was higher than found previously. Litter quality influenced the difference between microbial and total decomposition, with total decomposition of more recalcitrant litter being more sensitive to temperature. Our projections suggest that (i) warming will enhance the microbial contribution to decomposition, increasing CO 2 outgassing and intensifying the warming trend, especially in colder regions; and (ii) riparian species composition will have a major influence on this process.

Continent‐Wide Drivers of Spatial Synchrony in Breeding Demographic Structure Across Wild Great Tit Populations - Joe P. Woodman; Stefan J. G. Vriend; Frank Adriaensen; Elena Álvarez; Alexander Artemyev; Emilio Barba; Malcolm D. Burgess; Samuel P. Caro; Laure Cauchard; Anne Charmantier; Ella F. Cole; Niels Dingemanse; et al. (Ecology Letters, 2025)
Variation in age structure influences population dynamics, yet we have limited understanding of the spatial scale at which its fluctuations are synchronised between populations. Using 32 great tit populations, spanning 4° W–33° E and 35°–65° N involving > 130,000 birds across 67 years, we quantify spatial synchrony in breeding demographic structure (subadult vs. adult breeders) and its drivers. We show that larger clutch sizes, colder winters, and larger beech crops lead to younger populations. We report distance‐dependent synchrony of demographic structure, maintained at approximately 650 km. Despite covariation with demographic structure, we do not find evidence for environmental variables influencing the scale of synchrony, except for beech masting. We suggest that local ecological and density‐dependent dynamics impact how environmental variation interacts with demographic structure, influencing estimates of the environment's effect on synchrony. Our analyses demonstrate the operation of synchrony in demographic structure over large scales, with implications for age‐dependent demography in populations.

Corrigendum to “Potential groundwater contamination from oil drilling in the Okavango” [Phys. Chem. Earth Parts A/B/C 131 (2023) 13430] - R. Sheldon; S. Esterhuyse; A. Lukas; S. Greenwood (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Phylogeny and historical biogeography of the swallow family (Hirundinidae) inferred from comparisons of thousands of UCE loci - Drew R. Schield; Clare E. Brown; Subir B. Shakya; Gina M. Calabrese; Rebecca J. Safran; Frederick H. Sheldon (Molecular Phylogenetics and Evolution, 2024)

A machine learning classification of meteorite spectra applied to understanding asteroids - M. Darby Dyar; Sydney M. Wallace; Thomas H. Burbine; Daniel R. Sheldon (Icarus, 2023)

Potential groundwater contamination from oil drilling in the Okavango - R. Sheldon; S. Esterhuyse; A. Lukas; S. Greenwood (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Quantifying long‐term phenological patterns of aerial insectivores roosting in the Great Lakes region using weather surveillance radar - Yuting Deng; Maria Carolina T. D. Belotti; Wenlong Zhao; Zezhou Cheng; Gustavo Perez; Elske Tielens; Victoria F. Simons; Daniel R. Sheldon; Subhransu Maji; Jeffrey F. Kelly; Kyle G. Horton (Global Change Biology, 2023)
Organisms have been shifting their timing of life history events (phenology) in response to changes in the emergence of resources induced by climate change. Yet understanding these patterns at large scales and across long time series is often challenging. Here we used the US weather surveillance radar network to collect data on the timing of communal swallow and martin roosts and evaluate the scale of phenological shifts and its potential association with temperature. The discrete morning departures of these aggregated aerial insectivores from ground‐based roosting locations are detected by radars around sunrise. For the first time, we applied a machine learning algorithm to automatically detect and track these large‐scale behaviors. We used 21 years of data from 12 weather surveillance radar stations in the Great Lakes region to quantify the phenology in roosting behavior of aerial insectivores at three spatial levels: local roost cluster, radar station, and across the Great Lakes region. We show that their peak roosting activity timing has advanced by 2.26 days per decade at the regional scale. Similar signals of advancement were found at the station scale, but not at the local roost cluster scale. Air temperature trends in the Great Lakes region during the active roosting period were predictive of later stages of roosting phenology trends (75% and 90% passage dates). Our study represents one of the longest‐term broad‐scale phenology examinations of avian aerial insectivore species responding to environmental change and provides a stepping stone for examining potential phenological mismatches across trophic levels at broad spatial scales.

Temperature synchronizes temporal variation in laying dates across European hole‐nesting passerines - Stefan J. G. Vriend; Vidar Grøtan; Marlène Gamelon; Frank Adriaensen; Markus P. Ahola; Elena Álvarez; Liam D. Bailey; Emilio Barba; Jean‐Charles Bouvier; Malcolm D. Burgess; Andrey Bushuev; Carlos Camacho; et al. (Ecology, 2023)
Identifying the environmental drivers of variation in fitness‐related traits is a central objective in ecology and evolutionary biology. Temporal fluctuations of these environmental drivers are often synchronized at large spatial scales. Yet, whether synchronous environmental conditions can generate spatial synchrony in fitness‐related trait values (i.e., correlated temporal trait fluctuations across populations) is poorly understood. Using data from long‐term monitored populations of blue tits ( Cyanistes caeruleus , n = 31), great tits ( Parus major , n = 35), and pied flycatchers ( Ficedula hypoleuca , n = 20) across Europe, we assessed the influence of two local climatic variables (mean temperature and mean precipitation in February–May) on spatial synchrony in three fitness‐related traits: laying date, clutch size, and fledgling number. We found a high degree of spatial synchrony in laying date but a lower degree in clutch size and fledgling number for each species. Temperature strongly influenced spatial synchrony in laying date for resident blue tits and great tits but not for migratory pied flycatchers. This is a relevant finding in the context of environmental impacts on populations because spatial synchrony in fitness‐related trait values among populations may influence fluctuations in vital rates or population abundances. If environmentally induced spatial synchrony in fitness‐related traits increases the spatial synchrony in vital rates or population abundances, this will ultimately increase the risk of extinction for populations and species. Assessing how environmental conditions influence spatiotemporal variation in trait values improves our mechanistic understanding of environmental impacts on populations.

Caldera-like features located over the Panikkar Seamount and adjacent regions in the Laxmi Basin, eastern Arabian Sea - J John Savio; V Yatheesh; R Sheldon; M Kallathian; Pratima Kessarkar; Kuldeep Kumar; P Mahesh; Subhashree Mishra; Swati Verma (Journal of Earth System Science, 2022)

Perceived Barriers to the Use of Assisted Colonization for Climate Sensitive Species in the Hawaiian Islands - Shannon N. Rivera; Lucas Berio Fortini; Sheldon Plentovich; Melissa R. Price (Environmental Management, 2021)
Conservation actions to safeguard climate change vulnerable species may not be utilized due to a variety of perceived barriers. Assisted colonization, the intentional movement and release of an organism outside its historical range, is one tool available for species predicted to lose habitat under future climate change scenarios, particularly for single island or single mountain range endemic species. Despite the existence of policies that allow for this action, to date, assisted colonization has rarely been utilized for species of conservation concern in the Hawaiian Islands. Given the potential for climate driven biodiversity loss, the Hawaiian Islands are a prime location for the consideration of adaptation strategies. We used first-person interviews with conservation decision makers, managers, and scientists who work with endangered species in the Hawaiian Islands to identify perceived barriers to the use of assisted colonization. We found that assisted colonization was often not considered or utilized due to a lack of expertize with translocations; ecological risk and uncertainty, economic constraints, concerns regarding policies and permitting, concerns with public perception, and institutional resistance. Therefore, conservation planners may benefit from decision tools that integrate risk and uncertainty into decision models, and compare potential outcomes among conservation actions under consideration, including assisted colonization. Within a decision framework that addresses concerns, all conservation actions for climate sensitive species, including assisted colonization, may be considered in a timely manner.

Rat corneal endothelial cell migration during wound repair on the basement membrane depends more on the PI-3K pathway than the cdc-42 pathway or actin stress fibers - Sheldon R. Gordon; Geoffrey H. Gordon; Samantha Dimovski (Cell and Tissue Research, 2020)

Biotic interactions help explain variation in elevational range limits of birds among Bornean mountains - Ryan C. Burner; Andy J. Boyce; David Bernasconi; Alison R. Styring; Subir B. Shakya; Chandradewana Boer; Mustafa Abdul Rahman; Thomas E. Martin; Frederick H. Sheldon (Journal of Biogeography, 2020)
Aim Physiological tolerances and biotic interactions along habitat gradients are thought to influence species occurrence. Distributional differences caused by such forces are particularly noticeable on tropical mountains, where high species turnover along elevational gradients occurs over relatively short distances and elevational distributions of particular species can shift among mountains. Such shifts are interpreted as evidence of the importance of spatial variation in interspecific competition and habitat or climatic gradients. To assess the relative importance of competition and compression of habitat and climatic zones in setting range limits, we examined differences in elevational ranges of forest bird species among four Bornean mountains with distinct features. Location Bornean mountains Kinabalu, Mulu, Pueh and Topap Oso. Taxon Rain forest bird communities along elevational gradients. Methods We surveyed the elevational ranges of rain forest birds on four mountains in Borneo to test which environmental variables—habitat zone compression or presence of likely competitors—best predicted differences in elevational ranges of species among mountains. For this purpose, we used two complementary tests: a comparison of elevational range limits between pairs of mountains, and linear mixed models with naïve occupancy as the response variable. Results We found that lowland species occur higher in elevation on two small mountains compared to Mt. Mulu. This result is inconsistent with the expectation that distributions of habitats are elevationally compressed on small mountains, but is consistent with the hypothesis that a reduction in competition (likely diffuse) on short mountains, which largely lack montane specialist species, allows lowland species to occur higher in elevation. The relative influence of competition changes with elevation, and the correlation between lower range limits of montane species and the distribution of their competitors was weaker than in lowland species. Main conclusions These findings provide support for the importance of biotic interactions in setting elevational range limits of tropical bird species, although abiotic gradients explain the majority of distribution patterns. Thus, models predicting range shifts under climate change scenarios must include not only climatic variables, as is currently most common, but also information on potentially resulting changes in species interactions, especially for lowland species.

Occupancy patterns and upper range limits of lowland Bornean birds along an elevational gradient - Ryan C. Burner; Alison R. Styring; Mustafa A. Rahman; Frederick H. Sheldon (Journal of Biogeography, 2019)
Aim The traditional view of species’ distributions is that they are less abundant near the edges of their ranges and more abundant towards the centre. Testing this pattern is difficult because of the complexity of distributions across wide geographical areas. An alternative strategy, however, is to measure species’ distributional patterns along elevational gradients. We applied this strategy to examine whether lowland forest birds are indeed less common near their upper range limits on a Bornean mountain, and tested co‐occurrence patterns among species for potential causes of attenuation, including signatures of habitat selection and competition at the periphery of their ranges. Location Mt. Mulu, Borneo. Taxon Rain forest birds. Methods We surveyed lowland forest birds on Mt. Mulu (2,376 m), classified their elevation‐occupancy distributions using Huisman–Olff–Fresco (HOF) models, and examined co‐occurrence patterns of species pairs for signatures of shared habitat patches and interspecific competition. Results For 39 of 50 common species, occupancy was highest at sea level then gradually declined near their upper range edges, in keeping with a “rare periphery” hypothesis. With respect to habitat selection, lowland species do not appear to cluster together at sites of patchy similar habitat near their upper range limits; neither are most lowland species segregated from potential montane competitors where ranges overlap. Main conclusions High relative abundance at sea level implies that species inhabit “truncated niches” and are not currently near the limits of their fundamental niche, unless unknown critical response thresholds exist. However, indirect effects of increasing temperature predicted under climate change scenarios could still influence lower range limits of lowland species indirectly by altering habitat, precipitation regimes and competitive interactions. The lack of non‐random co‐occurrence patterns implies that patchy habitat and simple pairwise species interactions are unlikely to be responsible for upper range limits in most species; diffuse competition across diverse rain forest bird communities could still play a role.

Self-initiated continuation of and adherence to HIV pre-exposure prophylaxis (PrEP) after PrEP demonstration project roll-off in men who have sex with men: associations with risky decision making, impulsivity/disinhibition, and sensation seeking - Martin Hoenigl; Erin Morgan; Donald Franklin; Peter L. Anderson; Elizabeth Pasipanodya; Matthew Dawson; Marvin Hanashiro; Eric E. Ellorin; Jill Blumenthal; Robert Heaton; David J. Moore; Sheldon R. Morris (Journal of NeuroVirology, 2019)

Accounting for interspecific competition and age structure in demographic analyses of density dependence improves predictions of fluctuations in population size - Marlène Gamelon; Stefan J. G. Vriend; Steinar Engen; Frank Adriaensen; André A. Dhondt; Simon R. Evans; Erik Matthysen; Ben C. Sheldon; Bernt‐Erik Sæther (Ecology Letters, 2019)
Understanding species coexistence has long been a major goal of ecology. Coexistence theory for two competing species posits that intraspecific density dependence should be stronger than interspecific density dependence. Great tits and blue tits are two bird species that compete for food resources and nesting cavities. On the basis of long‐term monitoring of these two competing species at sites across Europe, combining observational and manipulative approaches, we show that the strength of density regulation is similar for both species, and that individuals have contrasting abilities to compete depending on their age. For great tits, density regulation is driven mainly by intraspecific competition. In contrast, for blue tits, interspecific competition contributes as much as intraspecific competition, consistent with asymmetric competition between the two species. In addition, including age‐specific effects of intra‐ and interspecific competition in density‐dependence models improves predictions of fluctuations in population size by up to three times.

Leveraging community-based participatory research capacity to recruit Pacific Islanders into a genetics study - Pearl A. McElfish; Marie-Rachelle Narcisse; Christopher R. Long; Britni L. Ayers; Nicola L. Hawley; Nia Aitaoto; Sheldon Riklon; L. Joseph Su; Shumona Z. Ima; Ralph O. Wilmoth; Thomas K. Schulz; Susan Kadlubar (Journal of Community Genetics, 2017)

Social and spatial effects on genetic variation between foraging flocks in a wild bird population - Reinder Radersma; Colin J. Garroway; Anna W. Santure; Isabelle de Cauwer; Damien R. Farine; Jon Slate; Ben C. Sheldon (Molecular Ecology, 2017)
Social interactions are rarely random. In some instances, animals exhibit homophily or heterophily, the tendency to interact with similar or dissimilar conspecifics, respectively. Genetic homophily and heterophily influence the evolutionary dynamics of populations, because they potentially affect sexual and social selection. Here, we investigate the link between social interactions and allele frequencies in foraging flocks of great tits ( Parus major ) over three consecutive years. We constructed co‐occurrence networks which explicitly described the splitting and merging of 85,602 flocks through time (fission–fusion dynamics), at 60 feeding sites. Of the 1,711 birds in those flocks, we genotyped 962 individuals at 4,701 autosomal single nucleotide polymorphisms ( SNP s). By combining genomewide genotyping with repeated field observations of the same individuals, we were able to investigate links between social structure and allele frequencies at a much finer scale than was previously possible. We explicitly accounted for potential spatial effects underlying genetic structure at the population level. We modelled social structure and spatial configuration of great tit fission–fusion dynamics with eigenvector maps. Variance partitioning revealed that allele frequencies were strongly affected by group fidelity (explaining 27%–45% of variance) as individuals tended to maintain associations with the same conspecifics. These conspecifics were genetically more dissimilar than expected, shown by genomewide heterophily for pure social (i.e., space‐independent) grouping preferences. Genomewide homophily was linked to spatial configuration, indicating spatial segregation of genotypes. We did not find evidence for homophily or heterophily for putative socially relevant candidate genes or any other SNP markers. Together, these results demonstrate the importance of distinguishing social and spatial processes in determining population structure.

The effect of salinity on plant-available water - Anna R. Sheldon; Ram C. Dalal; Gunnar Kirchhof; Peter M. Kopittke; Neal W. Menzies (Plant and Soil, 2017)

Groundwater cooling of a supercomputer in Perth, Western Australia: hydrogeological simulations and thermal sustainability - Heather A. Sheldon; Peter M. Schaubs; Praveen K. Rachakonda; Michael G. Trefry; Lynn B. Reid; Daniel R. Lester; Guy Metcalfe; Thomas Poulet; Klaus Regenauer-Lieb (Hydrogeology Journal, 2015)

Replicated analysis of the genetic architecture of quantitative traits in two wild great tit populations - Anna W. Santure; Jocelyn Poissant; Isabelle De Cauwer; Kees van Oers; Matthew R. Robinson; John L. Quinn; Martien A. M. Groenen; Marcel E. Visser; Ben C. Sheldon; Jon Slate (Molecular Ecology, 2015)
Currently, there is much debate on the genetic architecture of quantitative traits in wild populations. Is trait variation influenced by many genes of small effect or by a few genes of major effect? Where is additive genetic variation located in the genome? Do the same loci cause similar phenotypic variation in different populations? Great tits ( Parus major ) have been studied extensively in long‐term studies across Europe and consequently are considered an ecological ‘model organism’. Recently, genomic resources have been developed for the great tit, including a custom SNP chip and genetic linkage map. In this study, we used a suite of approaches to investigate the genetic architecture of eight quantitative traits in two long‐term study populations of great tits—one in the Netherlands and the other in the United Kingdom. Overall, we found little evidence for the presence of genes of large effects in either population. Instead, traits appeared to be influenced by many genes of small effect, with conservative estimates of the number of contributing loci ranging from 31 to 310. Despite concordance between population‐specific heritabilities, we found no evidence for the presence of loci having similar effects in both populations. While population‐specific genetic architectures are possible, an undetected shared architecture cannot be rejected because of limited power to map loci of small and moderate effects. This study is one of few examples of genetic architecture analysis in replicated wild populations and highlights some of the challenges and limitations researchers will face when attempting similar molecular quantitative genetic studies in free‐living populations.

Inferring social structure from temporal data - Ioannis Psorakis; Bernhard Voelkl; Colin J. Garroway; Reinder Radersma; Lucy M. Aplin; Ross A. Crates; Antica Culina; Damien R. Farine; Josh A. Firth; Camilla A. Hinde; Lindall R. Kidd; Nicole D. Milligan; et al. (Behavioral Ecology and Sociobiology, 2015)

Spatial mapping of evapotranspiration over Devils Lake basin with SEBAL: application to flood mitigation via irrigation of agricultural crops - Dean D. Steele; Bryan P. Thoreson; David G. Hopkins; Byron A. Clark; Sheldon R. Tuscherer; R. Gautam (Irrigation Science, 2015)

Developing a Longitudinal Cancer Nursing Education Program in Honduras - Lisa Kennedy Sheldon; Barbara Wise; Julie R. Carlson; Cynthia Dowds; Vanessa Sarchet; Jose Angel Sanchez (Journal of Cancer Education, 2013)

Individual personalities predict social behaviour in wild networks of great tits ( Parus major) - L. M. Aplin; D. R. Farine; J. Morand‐Ferron; E. F. Cole; A. Cockburn; B. C. Sheldon (Ecology Letters, 2013)
Social environments have an important effect on a range of ecological processes, and form a crucial component of selection. However, little is known of the link between personality, social behaviour and population structure. We combine a well‐understood personality trait with large‐scale social networks in wild songbirds, and show that personality underpins multiple aspects of social organisation. First, we demonstrate a relationship between network centrality and personality with ‘proactive’ (fast‐exploring) individuals associating weakly with greater numbers of conspecifics and moving between flocks. Second, temporal stability of associations relates to personality: ‘reactive’ (slow‐exploring) birds form synergistically stable relationships. Finally, we show that personality influences social structure, with males non‐randomly distributed across groups. These results provide strong evidence that songbirds follow alternative social strategies related to personality. This has implications not only for the causes of social network structure but also for the strength and direction of selection on personality in natural populations.

Dual-mixed HIV-1 coreceptor tropism and HIV-associated neurocognitive deficits - Sheldon R. Morris; Steven Paul Woods; Reena Deutsch; Susan J. Little; Gabriel Wagner; Erin E. Morgan; Robert K. Heaton; Scott L. Letendre; Igor Grant; Davey M. Smith (Journal of NeuroVirology, 2013)

Partitioning of genetic variation across the genome using multimarker methods in a wild bird population - Matthew R. Robinson; Anna W. Santure; Isabelle DeCauwer; Ben C. Sheldon; Jon Slate (Molecular Ecology, 2013)
The underlying basis of genetic variation in quantitative traits, in terms of the number of causal variants and the size of their effects, is largely unknown in natural populations. The expectation is that complex quantitative trait variation is attributable to many, possibly interacting, causal variants, whose effects may depend upon the sex, age and the environment in which they are expressed. A recently developed methodology in animal breeding derives a value of relatedness among individuals from high‐density genomic marker data, to estimate additive genetic variance within livestock populations. Here, we adapt and test the effectiveness of these methods to partition genetic variation for complex traits across genomic regions within ecological study populations where individuals have varying degrees of relatedness. We then apply this approach for the first time to a natural population and demonstrate that genetic variation in wing length in the great tit ( P arus major ) reflects contributions from multiple genomic regions. We show that a polygenic additive mode of gene action best describes the patterns observed, and we find no evidence of dosage compensation for the sex chromosome. Our results suggest that most of the genomic regions that influence wing length have the same effects in both sexes. We found a limited amount of genetic variance in males that is attributed to regions that have no effects in females, which could facilitate the sexual dimorphism observed for this trait. Although this exploratory work focuses on one complex trait, the methodology is generally applicable to any trait for any laboratory or wild population, paving the way for investigating sex‐, age‐ and environment‐specific genetic effects and thus the underlying genetic architecture of phenotype in biological study systems.

Genomic dissection of variation in clutch size and egg mass in a wild great tit ( Parus major ) population - Anna W. Santure; Isabelle De Cauwer; Matthew R. Robinson; Jocelyn Poissant; Ben C. Sheldon; Jon Slate (Molecular Ecology, 2013)
Clutch size and egg mass are life history traits that have been extensively studied in wild bird populations, as life history theory predicts a negative trade‐off between them, either at the phenotypic or at the genetic level. Here, we analyse the genomic architecture of these heritable traits in a wild great tit ( Parus major ) population, using three marker‐based approaches – chromosome partitioning, quantitative trait locus ( QTL ) mapping and a genome‐wide association study ( GWAS ). The variance explained by each great tit chromosome scales with predicted chromosome size, no location in the genome contains genome‐wide significant QTL , and no individual SNP s are associated with a large proportion of phenotypic variation, all of which may suggest that variation in both traits is due to many loci of small effect, located across the genome. There is no evidence that any regions of the genome contribute significantly to both traits, which combined with a small, nonsignificant negative genetic covariance between the traits, suggests the absence of genetic constraints on the independent evolution of these traits. Our findings support the hypothesis that variation in life history traits in natural populations is likely to be determined by many loci of small effect spread throughout the genome, which are subject to continued input of variation by mutation and migration, although we cannot exclude the possibility of an additional input of major effect genes influencing either trait.

Breeding ecology of the globally threatened Sociable Lapwing Vanellus gregarius and the demographic drivers of recent declines - Rob D. Sheldon; Johannes Kamp; Maxim A. Koshkin; Ruslan S. Urazaliev; Timur K. Iskakov; Rob H. Field; Albert R. Salemgareev; Valery V. Khrokov; Vasily A. Zhuly; Sergey L. Sklyarenko; Paul F. Donald (Journal of Ornithology, 2013)

Trait-dependent declines of species following conversion of rain forest to oil palm plantations - Michael J. M. Senior; Keith C. Hamer; Simon Bottrell; David P. Edwards; Tom M. Fayle; Jennifer M. Lucey; Peter J. Mayhew; Robert Newton; Kelvin S.-H. Peh; Frederick H. Sheldon; Christopher Stewart; Alison R. Styring; et al. (Biodiversity and Conservation, 2013)

The potential for convection and implications for geothermal energy in the Perth Basin, Western Australia - Heather A. Sheldon; Brendan Florio; Michael G. Trefry; Lynn B. Reid; Ludovic P. Ricard; K. Ameed R. Ghori (Hydrogeology Journal, 2012)

Phylogeography and species biogeography of montane Great Basin stoneflies - ALICIA S. SCHULTHEIS; JACKIE Y. BOOTH; LISA R. PERLMUTTER; JASON E. BOND; ANDREW L. SHELDON (Molecular Ecology, 2012)
Sky islands are ideal systems for determining the effects of climatic oscillations on species distributions and genetic structure. Our study focused on montane stonefly populations in the Great Basin of western North America. We used niche‐based distribution modelling, phylogeography and traditional species‐based biogeography to test several hypotheses as follows: (i) genetic differentiation among Doroneuria baumanni populations will be independent of hydrologic connectivity (headwater model); (ii) Sky islands were colonized when habitat was more continuous and populations likely experienced multiple expansions and contractions; (iii) Colonization events were coincident with the late Pleistocene and Holocene; and (iv) Shared topography and climate history will result in concordant patterns of genetic differentiation in D. baumanni and occurrences of 32 stonefly species across the region. Overall, Φ ST ’s and coalescent‐based estimates of migration were consistent with the headwater model. Maximum likelihood and Bayesian gene trees identified three major nonoverlapping east‐west clades. Distribution modelling indicated more suitable habitat in the Great Basin during the Last Glacial Maximum than at present, but none during the last interglacial period. Demographic analyses showed evidence of population expansion in one of the three major east–west clades. Intra‐clade divergence times (60 000–183 000 ybp) were well within the late Pleistocene while among‐clade divergence times (499 000–719 000 ybp) were deeper. Genetic differentiation in D. baumanni and distributions of stonefly species were significantly concordant. These results imply that climatic oscillations have played major roles in shaping the genetic structure and distributions of Great Basin stoneflies, but that divergence among clades occurred much earlier than our late Pleistocence/early Holocene predictions.

Elevated summer temperatures delay spawning and reduce redd construction for resident brook trout ( S alvelinus fontinalis ) - Dana R. Warren; Jason M. Robinson; Daniel C. Josephson; Daniel R. Sheldon; Clifford E. Kraft (Global Change Biology, 2012)
Redd (nest) surveys for resident brook trout ( S alvelinus fontinalis ) were conducted annually in a mountain lake in northern New York for 11 years with multiple surveys conducted during the spawning season in eight of those years. Repeated surveys throughout the spawning season allowed us to fit an individually based parametric model and estimate the day of year on which spawning was initiated, reached its midpoint, and ended during each year. Spawning phenology was then assessed relative to (1) mean of maximum daily air temperature and (2) mean of maximum daily water temperature at the lake bottom during summer in each year using a linear model. Elevated temperatures in summer were correlated with a delay in spawning and a reduction in the total number of redds constructed. Increasing the summer mean of maximum daily air temperatures by 1 °C delayed spawning by approximately 1 week and decreased the total number of redds constructed by nearly 65. Lake spawning brook trout select redd sites based on the presence of discharging groundwater that is relatively constant in temperature within and across years, leading to relatively consistent egg incubation times. Therefore, delayed spawning is likely to delay fry emergence, which could influence emergence synchrony with prey items. This work highlights non‐lethal and sub‐lethal effects of elevated summer temperatures on native resident salmonids in aquatic environments with limited thermal refugia.

A comparison between SSM/I passive microwave melt onset dates and satellite-derived albedo melt onset dates in the Arctic - Mark R. Anderson; Jessica L. Busse; Sheldon D. Drobot (International Journal of Remote Sensing, 2012)

Corrigendum - J. R. CHAPMAN; S. NAKAGAWA; D. W. COLTMAN; J. SLATE; B. C. SHELDON (Molecular Ecology, 2011)

Interaction between Cu toxicity and P deficiency in soil-grown cowpea (Vigna unguiculata (L.) Walp.) - Tia R. Northfield; Anna R. Sheldon; Peter M. Kopittke; Neal W. Menzies (Plant and Soil, 2011)

Neurocognitive functioning in acute or early HIV infection - David J. Moore; Scott L. Letendre; Sheldon Morris; Anya Umlauf; Reena Deutsch; Davey M. Smith; Susan Little; Alexandra Rooney; Donald R. Franklin; Ben Gouaux; Shannon LeBlanc; Debra Rosario; et al. (Journal of NeuroVirology, 2011)

A quantitative review of heterozygosity–fitness correlations in animal populations - J. R. CHAPMAN; S. NAKAGAWA; D. W. COLTMAN; J. SLATE; B. C. SHELDON (Molecular Ecology, 2009)
The ease of obtaining genotypic data from wild populations has renewed interest in the relationship between individual genetic diversity and fitness‐related traits (heterozygosity–fitness correlations, or HFC). Here we present a comprehensive meta‐analysis of HFC studies using powerful multivariate techniques which account for nonindependence of data. We compare these findings with those from univariate techniques, and test the influence of a range of factors hypothesized to influence the strength of HFCs. We found small but significantly positive effect sizes for life‐history, morphological, and physiological traits; while theory predicts higher mean effect sizes for life‐history traits, effect size did not differ consistently with trait type. Newly proposed measures of variation were no more powerful at detecting relationships than multilocus heterozygosity, and populations predicted to have elevated inbreeding variance did not exhibit higher mean effect sizes. Finally, we found evidence for publication bias, with studies reporting weak, nonsignificant effects being under‐represented in the literature. In general, our review shows that HFC studies do not generally reveal patterns predicted by population genetic theory, and are of small effect (less than 1% of the variance in phenotypic characters explained). Future studies should use more genetic marker data and utilize sampling designs that shed more light on the biological mechanisms that may modulate the strength of association, for example by contrasting the strength of HFCs in mainland and island populations of the same species, investigating the role of environmental stress, or by considering how selection has shaped the traits under investigation.

Soybean agglutinin binding to corneal endothelial cell surfaces disrupts in situ monolayer integrity and actin organization and interferes with wound repair - Sheldon R. Gordon; Meredith Wood (Cell and Tissue Research, 2009)

Avian haematozoan parasites and their associations with mosquitoes across Southwest Pacific Islands - F. ISHTIAQ; L. GUILLAUMOT; S. M. CLEGG; A. B. PHILLIMORE; R. A. BLACK; I. P. F. OWENS; N. I. MUNDY; B. C. SHELDON (Molecular Ecology, 2008)
The degree to which haematozoan parasites can exploit a range of vectors and hosts has both ecological and evolutionary implications for their transmission and biogeography. Here we explore the extent to which closely related mosquito species share the same or closely related haematozoan parasites, and examine the overlap in parasite lineages with those isolated from avian hosts, Zosterops species, sampled across the same study sites. Mosquito samples were collected and analysed (14 species, n = 804) from four islands in Vanuatu and the main island of New Caledonia. Using polymerase chain reaction, 15.5% (14/90) of pooled mosquito (thoracic) samples showed positive amplifications. Subsequent phylogenetic analysis of the cytochrome b gene identified four genetically distinct Plasmodium and two Haemoproteus lineages from these samples, five of which were identical to parasite lineages ( n = 21) retrieved from the avian hosts. We found that three Plasmodium lineages differing by a maximum of 0.9% sequence divergence were recovered from different species and genera of mosquitoes and two Haemoproteus lineages differing by 4.6% sequence divergence were carried by 10 distantly related (11–21% divergent) mosquito species. These data suggest a lack of both cospeciation and invertebrate host conservatism. Without experimental demonstration of the transmission cycle, it is not possible to establish whether these mosquitoes are the biological vectors of isolated parasite lineages, reflecting a limitation of a purely polymerase chain reaction‐based approach. Nonetheless, our results raise the possibility of a new transmission pathway and highlight extensive invertebrate host shifts in an insular mosquito–parasite system.

Interspecific Patterns of Genetic Diversity in Birds: Correlations with Extinction Risk - SIMON R. EVANS; BEN C. SHELDON (Conservation Biology, 2008)
Birds are frequently used as indicators of ecosystem health and are the most comprehensively studied class in the animal kingdom. Nevertheless, a comprehensive, interspecific assessment of the correlates of avian genetic diversity is lacking, even though indices of genetic diversity are of considerable interest in the conservation of threatened species. We used published data on variation at microsatellite loci from 194 bird species to examine correlates of diversity, particularly with respect to conservation status and population size. We found a significant decline in mean heterozygosity with increasing extinction risk, and showed, by excluding species whose heterozygosity values were calculated with heterospecific primers, that this relationship was not dependent on ascertainment bias. Results of subsequent regression analyses suggested that smaller population sizes of threatened species were largely responsible for this relationship. Thus, bird species at risk of extinction are relatively depauperate in terms of neutral genetic diversity, which is expected to make population recovery more difficult if it reflects adaptive genetic variation. Conservation policy will need to minimize further loss of diversity if the chances of saving threatened species are to be maximized.

Senescence rates are determined by ranking on the fast–slow life‐history continuum - Owen R. Jones; Jean‐Michel Gaillard; Shripad Tuljapurkar; Jussi S. Alho; Kenneth B. Armitage; Peter H. Becker; Pierre Bize; Jon Brommer; Anne Charmantier; Marie Charpentier; Tim Clutton‐Brock; F. Stephen Dobson; et al. (Ecology Letters, 2008)
Comparative analyses of survival senescence by using life tables have identified generalizations including the observation that mammals senesce faster than similar‐sized birds. These generalizations have been challenged because of limitations of life‐table approaches and the growing appreciation that senescence is more than an increasing probability of death. Without using life tables, we examine senescence rates in annual individual fitness using 20 individual‐based data sets of terrestrial vertebrates with contrasting life histories and body size. We find that senescence is widespread in the wild and equally likely to occur in survival and reproduction. Additionally, mammals senesce faster than birds because they have a faster life history for a given body size. By allowing us to disentangle the effects of two major fitness components our methods allow an assessment of the robustness of the prevalent life‐table approach. Focusing on one aspect of life history – survival or recruitment – can provide reliable information on overall senescence.

Defining the expression pattern of the LGI1 gene in BAC transgenic mice - Karen Head; Shiaoching Gong; Sheldon Joseph; Cuidong Wang; Tania Burkhardt; Michael R. Rossi; Jeffrey LaDuca; Sei-Ichi Matsui; Mary Vaughan; David G. Hicks; Nathaniel Heintz; John K. Cowell (Mammalian Genome, 2007)

The Effect of Copper Toxicity on the Growth and Root Morphology of Rhodes Grass (Chloris gayana Knuth.) in Resin Buffered Solution Culture - A. R. Sheldon; N. W. Menzies (Plant and Soil, 2005)

Molecular Systematics and Evolution of the Growth Hormone Introns in the Salmoninae - Ruth B. Phillips; Makoto P. Matsuoka; Nick R. Konkol; Sheldon McKay (Environmental Biology of Fishes, 2004)

Speciation, introgressive hybridization and nonlinear rate of molecular evolution in flycatchers - Glenn‐Peter Sætre; Thomas Borge; Johan Lindell; Truls Moum; Craig R. Primmer; Ben C. Sheldon; Jon Haavie; Arild Johnsen; Hans Ellegren (Molecular Ecology, 2001)
Evolutionary history of Muscicapidae flycatchers is inferred from nuclear and mitochondrial DNA (mtDNA) sequence comparisons and population genetic analysis of nuclear and mtDNA markers. Phylogenetic reconstruction based on sequences from the two genomes yielded similar trees with respect to the order at which the species split off. However, the genetic distances fitted a nonlinear, polynomial model reflecting diminishing divergence rate of the mtDNA sequences compared to the nuclear DNA sequences. This could be explained by Haldane’s rule because genetic isolation might evolve more rapidly on the mitochondrial rather than the nuclear genome in birds. This is because hybrid sterility of the heterogametic sex (females) would predate that of the homogametic sex (males), leading to sex biased introgression of nuclear genes. Analyses of present hybrid zones of pied ( Ficedula hypoleuca ) and collared flycatchers ( F. albicollis ) may indicate a slight sexual bias in rate of introgression, but the introgression rates were too low to allow proper statistical analyses. It is suggested, however, that the observed deviation from linearity can be explained by a more rapid mutational saturation of the mtDNA sequences than of the nuclear DNA sequences, as supported by analyses of third codon position transversions at two protein coding mtDNA genes. A phylogeographic scenario for the black and white flycatcher species is suggested based on interpretation of the genetic data obtained. Four species appear to have diverged from a common ancestor relatively simultaneously during the Pleistocene. After the last glaciation period, pied and collared flycatchers expanded their breeding ranges and eventually came into secondary contact in Central and Eastern Europe and on the Baltic Isles.

The identical 5' splice-site acceptor mutation in five attenuated APC families from Newfoundland demonstrates a founder effect - L. Spirio; J. Green; J. Robertson; M. Robertson; B. Otterud; J. Sheldon; E. Howse; R. Green; J. Groden; R. White; M. Leppert (Human Genetics, 1999)

The identical 5' splice-site acceptor mutation in five attenuated APC families from Newfoundland demonstrates a founder effect - L. Spirio; J. Green; J. Robertson; M. Robertson; B. Otterud; J. Sheldon; E. Howse; R. Green; J. Groden; R. White; M. Leppert (Human Genetics, 1999)

Residues of pentachlorophenol and other chlorinated contaminants in human tissues: Analysis by electron capture gas chromatography and electron capture negative ion mass spectrometry - Sheldon L. Wagner; Lucia R. Durand; Roderick D. Inman; Ulo Kiigemagi; Max L. Deinzer (Archives of Environmental Contamination and Toxicology, 1991)